2022
DOI: 10.3390/insects13020138
|View full text |Cite
|
Sign up to set email alerts
|

Stress Resistance Traits under Different Thermal Conditions in Drosophila subobscura from Two Altitudes

Abstract: Global warming and climate change are affecting many insect species in numerous ways. These species can develop diverse mechanisms as a response to variable environmental conditions. The rise in mean and extreme temperatures due to global warming and the importance of the population’s ability to adapt to temperature stress will further increase. In this study, we investigated thermal stress response, which is considered to be one of the crucial elements of population fitness and survival in fast-changing envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…As expected, each population varied in its CSR traits in a manner that could be interpreted as showing local environmental adaptation ( Table 1 ), an interpretation that is in keeping with much of the foregoing literature (e.g., Hoffmann et al., 2002 ; Sgrò et al., 2010 ; Kellerman et al., 2012b ; Erić et al., 2022 ). Flies from warmer or drier ecoregions generally withstand heat and/or desiccation better than flies from cooler sites and vice versa.…”
Section: Discussionsupporting
confidence: 82%
“…As expected, each population varied in its CSR traits in a manner that could be interpreted as showing local environmental adaptation ( Table 1 ), an interpretation that is in keeping with much of the foregoing literature (e.g., Hoffmann et al., 2002 ; Sgrò et al., 2010 ; Kellerman et al., 2012b ; Erić et al., 2022 ). Flies from warmer or drier ecoregions generally withstand heat and/or desiccation better than flies from cooler sites and vice versa.…”
Section: Discussionsupporting
confidence: 82%
“…We also detected a notable amount of sex-specific differentially expressed genes after heat stress. This could also be related to the differential thermal adaptation observed between males and females of Drosophila in previous studies ( Hsu et al 2020 ), the higher heat resistance observed in D. subobscura females ( Erić et al 2022 ), and the sex-specific response after a heat stress observed in other species ( Srikanth et al 2020 ; Bedulina et al 2021 ). It could also be influenced by the differential expression of genes involved in chromatin remodeling in females but not in males.…”
Section: Discussionmentioning
confidence: 79%
“…Their ability to survive periods of extreme heat directly depends on their heat tolerance (Bowler and Terblanche, 2008;Kingsolver et al, 2011;Klockmann et al, 2017;Radchuk et al, 2013), but also on their ability to survive other stressors occurring during heat waves such as resource shortage (Johansson et al, 2020;Maron et al, 2015). Effects of genetic background (Erić et al, 2022;Hoffmann et al, 2005;Sarup and Loeschcke, 2010) and phenotypic plasticity (Ghalambor et al, 2007;Hochachka and Somero, 2014;Leroi et al, 1994;Levins, 1969;Via et al, 1995) are known to affect stress resistance, but how plastic responses vary between individuals originating from different populations (i.e. genetic variation in plasticity) is still largely unknown.…”
Section: Introductionmentioning
confidence: 99%